Open label smoking cessation with varenicline is associated with decreased glutamate levels and functional changes in anterior cingulate cortex: preliminary findings - Muriah Dawn Wheelock; Meredith A Reid; Harrison eTo; David eWhite; Karen L Cropsey; Adrienne Carol Lahti (Frontiers Media S.A., 2014)
Rationale: Varenicline, the most effective single agent for smoking cessation, is a partial agonist at α4β2 nicotinic acetylcholine receptors. Increasing evidence implicates glutamate in the pathophysiology of addiction and one of the benefits of treatment for smoking cessation is the ability to regain cognitive control. Objective: To evaluate the effects of 12 week varenicline administration on glutamate levels in the dorsal anterior cingulate cortex (dACC) and functional changes within the cognitive control network.Methods: We used single-voxel proton magnetic resonance spectroscopy (1H-MRS) in the dACC and functional MRI (fMRI) during performance of a Stroop color-naming task before and after smoking cessation with varenicline in 11 healthy smokers (open label design). Using the dACC as a seed region, we evaluated functional connectivity changes using a psychophysiological interaction (PPI) analysis. Results: We observed a significant decrease in dACC glutamate + glutamine (Glx)/Cr levels as well as significant blood oxygen level-dependent signal (BOLD) decreases in the rostral ACC/medial orbitofrontal cortex and precuneus/posterior cingulate cortex. These BOLD changes are suggestive of alterations in default mode network (DMN) function and are further supported by the results of the PPI analysis that revealed changes in connectivity between the dACC and regions of the DMN. Baseline measures of nicotine dependence and craving positively correlated with baseline Glx/Cr levels.Conclusions: These results suggest possible mechanisms of action for varenicline such as reduction in Glx levels in dACC and shifts in BOLD activities between large scale brain networks. They also suggest a role for ACC Glx in the modulation of behavior. Due to the preliminary nature of this study (lack of control group and small sample size), future studies are needed to replicate these findings.